Positive Selection Vectors to Generate Fused Genes for the Expression of His-Tagged Proteins - T. Van Reeth; P.-L. Drèze; J. Szpirer; C. Szpirer; P. Gabant (BioTechniques)
Epitope tagging simplifies detection, characterization and purification of proteins. Gene fusion to combine the coding region of a well-characterized epitope with the coding region for a protein of interest generally requires several subcloning steps. Alternatively, a PCR strategy can be used to generate such a chimeric gene. In addition to its simplicity, this approach allows one to limit the size of the multiple cloning sites present in conventional expression vectors, thus reducing the introduction of artifactual amino-acid sequences into the fused protein. In this communication, we describe new vectors that allow PCR cloning and selection of chimeric genes coding for N- or C-terminal His-tagged proteins. These vectors are based on the control of cell death CcdB direct selection technology and are well adapted to the cloning of blunt-ended PCR products that were generated by using thermostable polymerases that provide proofreading activity.